Method for preparing high-strength glass fiber plate by using flame-retardant fast-curing glass fiber cloth

By using composite flame retardant and composite curing agent in the preparation process of glass fiber boards, combined with modified phenolic resin, the problem of poor mechanical properties and flame retardant properties of existing glass fiber boards is solved, and high strength and high safety glass fiber board preparation is achieved.

CN119613779APending Publication Date: 2025-03-14JIUJIANG XUNWEI NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411871345.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The mechanical properties and flame retardant properties of existing fiberglass panels are poor, making it difficult to meet the needs of high strength and high safety.

Method used

The flame retardant and composite curing agent are used to improve the flame retardant and mechanical properties of glass fiberboard through ultrasonic dispersion and oil bath stirring, and the curing speed and strength of the resin are enhanced by modifying the phenolic resin.

Benefits of technology

It significantly improves the strength, flame retardant performance and curing speed of glass fiber boards, extends the service life of PCB circuit boards, and effectively blocks flame and heat transfer under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195843820000031
    Figure BDA0005195843820000031
  • Figure BDA0005195843820000051
    Figure BDA0005195843820000051
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength glass fiber plate by using flame-retardant fast-curing glass fabric, and belongs to the technical field of preparation of glass fiber plates. The preparation method of the high-strength glass fiber plate using the flame-retardant fast-curing glass fiber cloth comprises the following steps: step 1, adding a composite flame retardant into deionized water, carrying out ultrasonic dispersion, adding the glass fiber cloth, and drying to obtain the treated glass fiber cloth; 2, phenolic resin and benzoxazine resin are added into a container, then 4-dodecyl resorcinol is added, oil bath stirring and constant-temperature heat preservation reaction are carried out, then the container is cooled for reaction, after the reaction is finished, modified phenolic resin is obtained, the modified phenolic resin, a composite curing agent and a dispersing agent are mixed and stirred, and composite resin is obtained; 3, the treated glass fiber cloth is added into the composite resin to be soaked, taken out, placed in a mold, pressed and cured, and the high-strength glass fiber plate is obtained. The glass fiber plate prepared by the method has excellent mechanical property and flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass fiber board preparation, and in particular relates to a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth. Background Art

[0002] With the rapid development of modern electronic technology, PCB, as the core component of electronic equipment, its performance and quality directly affect the stability and reliability of the entire electronic equipment. In the production process of PCB circuit boards, the selection of substrates is crucial. It not only needs to have excellent electrical, thermal and mechanical properties, but also needs to meet special requirements such as environmental protection and flame retardancy. In recent years, flame retardant fast-curing Bosina has gradually become the preferred material for the production of high-strength glass fiber boards due to its unique performance and advantages, especially in the PCB circuit board industry, and its application prospects are becoming more and more broad.

[0003] Flame retardant fast curing fiberglass cloth is a high-performance textile made by special process. It combines the high strength of glass fiber and the fireproof performance of flame retardant, so that this material can maintain stable physical properties and is not easy to burn when facing extreme environments such as high temperature and flame, effectively preventing the spread of fire. This feature is particularly important in the PCB circuit board industry, because circuit boards will generate high temperatures during operation and even encounter fires in some extreme cases. Therefore, the use of flame retardant materials can effectively reduce the risk of fire and ensure the safe operation of electronic equipment.

[0004] Patent CN209944267U discloses a new type of high-efficiency heat dissipation single-sided PCB fiberglass board, including a board ladder, a plurality of LED light sources are arranged on the top surface of the board body, a plurality of fixing holes are arranged at equal distances on the top edge of the board body, a connecting hole is arranged at the center of the board body, a plurality of splicing slots are arranged at equal distances on the edge of the board body, and a support pad is arranged at each corresponding position of the bottom of the board body relative to the four linking slots. The invention adds a plurality of heat dissipation grooves on the back of the board body, and a heat dissipation strip with a thermal conductive silicone layer is designed in the heat dissipation groove, so that the heat on the board body can be quickly transferred to the heat dissipation strip, which facilitates the rapid heat dissipation of the heat on the heat dissipation strip. However, the flame retardant properties and mechanical properties of the fiberglass board prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, so as to solve the technical problem of poor mechanical properties and flame retardant properties of the glass fiber board in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a high-strength glass fiber board using a flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0008] Step 1: adding the composite flame retardant to deionized water, and after ultrasonic dispersion, adding glass fiber cloth, and drying to obtain treated glass fiber cloth;

[0009] Step 2: adding phenolic resin and benzoxazine resin into a container, then adding 4-dodecylresorcinol, stirring in an oil bath, reacting at a constant temperature, then cooling the container to react, after the reaction is completed, a modified phenolic resin is obtained, and the modified phenolic resin, a composite curing agent and a dispersant are mixed and stirred to obtain a composite resin;

[0010] In the above process, the benzoxazine resin and the phenolic resin undergo a copolymerization reaction, the active hydrogen of the phenolic resin catalyzes the ring opening of the benzoxazine, and the phenolic hydroxyl group of the ring-opened benzoxazine can react with the ortho and para positions of the phenolic resin to form a copolymer, and then the phenolic hydroxyl group of 4-dodecylresorcinol reacts with the active hydrogen in the copolymer to form a new chemical bond to obtain a modified phenolic resin; the addition of the modified phenolic resin can effectively improve the flame retardancy and mechanical properties of the resin.

[0011] Step 3: Add the treated glass fiber cloth into the composite resin for impregnation, take it out, place it in a mold, press it, and solidify it to obtain a high-strength glass fiber board.

[0012] Preferably, the method for preparing the composite flame retardant comprises the following steps:

[0013] Q1: Under a nitrogen atmosphere, add 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heat in an oil bath, stir mechanically, and then add phosphorus pentoxide. After the addition is completed, reduce the speed, increase the temperature to react, then continue to increase the temperature to react, add distilled water, increase the speed, hydrolyze, and obtain a crude product;

[0014] Q2: Add the crude product to anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide to the supernatant, filter, wash, and dry to obtain a composite flame retardant.

[0015] In the above process, 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether is used as the main raw material, phosphorus pentoxide is used as the phosphorylation agent, and a crude product containing a phosphate group is formed through an esterification reaction. Subsequently, potassium hydroxide is added to the crude product as an alkalizing agent, and the hydroxide ions in the potassium hydroxide react with the hydrogen ions in the crude product to neutralize and prepare a composite flame retardant, wherein the synthesis reaction formula of the composite flame retardant is as follows:

[0016]

[0017] The results of mass spectrometry analysis of the crude product were: m / z: 695.00 (100.0%), 696.01 (15.6%), 697.00 (4.6%), 697.01 (2.7%), 696.00 (1.2%).

[0018] Preferably, in Q1, the mass ratio of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether and phosphorus pentoxide is (22.62-33.94):(2.12-3.08), the oil bath heating temperature is 40-50°C, the mechanical stirring speed is 250-280rpm, the time for adding phosphorus pentoxide is 20-25min, the speed is reduced to 200-220rpm, the temperature of the heating reaction is 68-70°C, the heating time is 15-20min, the heating reaction time is 3.5-4h, the temperature of the heating reaction is continued to be 75-80°C, the speed is increased to 230-240rpm, and the hydrolysis time is 30-60min.

[0019] Preferably, in Q2, the usage ratio of the crude product and anhydrous ethanol is (1.84-2.32) g: (8-10) mL, the mass fraction of the anhydrous ethanol solution containing potassium hydroxide is 15 wt %, the drying temperature is 85-95° C., and the drying time is 48-72 h.

[0020] Preferably, in step 1, the usage ratio of the composite flame retardant and deionized water is (4-6) g: (10-13) mL, the ultrasonic dispersion time is 10-15 min, the drying temperature is 50-70° C., and the drying time is 8-10 h.

[0021] Preferably, in the step 2, the amount ratio of phenolic resin, benzoxazine resin and 4-dodecylresorcin is (3-5) g: (2-3) g: (0.25-0.75) g, the constant temperature insulation reaction temperature is 95-105° C., the reaction time is 2-3 h, the cooling reaction temperature is 50-55° C., the reaction time is 2-5 h, the amount ratio of modified phenolic resin, composite curing agent and dispersant is (510-625) g: (10-14) g: (5-9) g, and the mixing time is 2-4 h.

[0022] Preferably, the preparation method of the composite curing agent comprises the following steps:

[0023] S1: Add tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add tetrafluorophthalic acid, dicyclohexylcarbodiimide and 2-dimethylaminopyridine in sequence under an ice-water bath, stir thoroughly until completely dissolved, react, and filter to obtain reactant 1;

[0024] S2: Add hexamethylenediamine dissolved in tetrahydrofuran into a container, and slowly add reactant 1 under ice bath conditions. After the addition is completed, react, and then heat to continue the reaction. After the reaction is completed, rotary evaporate, dissolve, filter, wash, dry, filter, and rotary evaporate to obtain a composite curing agent.

[0025] In the above process, dicyclohexylcarbodiimide reacts with tetrafluorophthalic acid to obtain an intermediate, and then the intermediate reacts with 2-dimethylaminopyridine to obtain reactant 1, and then reactant 1 reacts with hexamethylenediamine to obtain a composite curing agent, wherein the synthetic reaction formula of the composite curing agent is as follows:

[0026]

[0027] Preferably, in S1, the dosage ratio of tetrahydrofuran, tetrafluorophthalic acid, dicyclohexylcarbodiimide and 2-dimethylaminopyridine is (250-300) mL: (11-12.2) g: (20-22.84) g: (5-6.16) g, the sufficient stirring time is 2-4 h, and the reaction time is 1-2 h.

[0028] Preferably, in S2, the dosage ratio of tetrahydrofuran, hexamethylenediamine and reactant 1 is (50-75) mL: (23.5-45) g: (12.45-15.68) g, the reaction time is 2-4 h, the heating reaction temperature is 60-80°C, the reaction time is 3-5 h, dichloromethane is added for dissolution, the mixture is washed with deionized water to pH = 7-8, and the mixture is dried with anhydrous sodium sulfate.

[0029] Preferably, in step three, the infiltration time is 3-5 hours.

[0030] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0031] 1. The present invention first uses 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether, phosphorus pentoxide and potassium hydroxide as raw materials to prepare a composite flame retardant, then uses tetrafluorophthalic acid, dicyclohexylcarbodiimide, 2-dimethylaminopyridine and hexamethylenediamine as raw materials to prepare a composite curing agent, then uses benzoxazine resin and 4-dodecylresorcinol to modify phenolic resin, and finally adds it to the preparation process of glass fiber board, which can effectively improve the strength, flame retardant performance and curing speed of glass fiber board, and applies it to PCB circuit board to effectively improve its service life.

[0032] 2. The present invention adds the prepared composite flame retardant to the preparation process of the glass fiber board, which can effectively improve its flame retardant properties. Under high temperature conditions, the phosphate group in the composite flame retardant will decompose to produce phosphoric acid, promote the dehydration and carbonization of the glass fiber cloth, form a dense coke layer, effectively block the flame and heat transfer, and at the same time, the phosphorus and nitrogen elements in the composite flame retardant are chemically combined with the fiber to enhance the structural stability and thermal stability. In addition, the free radical scavenger produced by the decomposition of the composite flame retardant can inhibit the flame chain reaction, reduce the combustion rate, and dilute the concentration of combustible gases by releasing gases such as water vapor and nitrogen. At the same time, the composite flame retardant can also form a viscous molten layer to slow down the melting and dripping of the glass fiber cloth. Its coke layer and molten layer have good thermal insulation properties, reduce heat conduction, and reduce the overall temperature of the glass fiber board, thereby comprehensively improving the flame retardant properties of the glass fiber board.

[0033] 3. The present invention adds a composite curing agent to the preparation process of the glass fiber board, which can not only improve its curing speed, but also improve its hardness and strength. The amide bonds in the composite curing agent have high reactivity with the functional groups in the resin. When the composite curing agent is added to the resin, the two undergo a cross-linking reaction to form a three-dimensional network structure. Since the functional groups in the composite curing agent have high reactivity, a cross-linking reaction can occur rapidly at a lower temperature, thereby accelerating the curing speed of the resin. The formed three-dimensional structure has a high cross-linking density and stability, thereby enhancing the interaction force between the resin molecules, improving the hardness and strength of the resin, and the fluoride ions contained in the composite curing agent can effectively improve the flame retardant properties of the glass fiber board. DETAILED DESCRIPTION

[0034] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1: This example discloses a method for preparing a composite flame retardant, comprising the following steps:

[0036] Q1: Under nitrogen atmosphere, 28.28 g of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether was added to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heated in an oil bath at 45°C, and mechanically stirred at 280 rpm. Then, 2.6 g of phosphorus pentoxide was added within 25 min. After the addition was completed, the speed was reduced to 220 rpm, and the temperature was raised to 70°C for reaction for 20 min, and then the temperature was continued to be raised to 80°C for reaction for 4 h. Distilled water was added, the speed was increased to 240 rpm, and hydrolysis was carried out for 45 min to obtain a crude product.

[0037] Q2: Add 2.08 g of the crude product to 9 mL of anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt%, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt% to the supernatant, filter, wash, and dry at 90°C for 72 h to obtain a composite flame retardant.

[0038] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0039] S1: Add 275 mL of tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add 11.6 g of tetrafluorophthalic acid, 21.42 g of dicyclohexylcarbodiimide and 5.58 g of 2-dimethylaminopyridine in an ice-water bath, stir well for 4 h until completely dissolved, react for 2 h, and filter to obtain reactant 1;

[0040] S2: Add 39.1 g of hexamethylenediamine dissolved in 62.5 mL of tetrahydrofuran into the container, and slowly add 14.55 g of reactant 1 under ice bath conditions. After the addition is completed, react for 4 hours, then heat to 70°C and continue to react for 5 hours. After the reaction is completed, evaporate the mixture, add dichloromethane to dissolve, filter, wash with deionized water to pH = 7, dry with anhydrous sodium sulfate, filter, and evaporate the mixture to obtain a composite curing agent.

[0041] This embodiment discloses a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0042] Step 1: Add 5 g of the composite flame retardant to 11.5 mL of deionized water, disperse it by ultrasonic for 15 min, add glass fiber cloth, and dry it at 70 ° C for 10 h to obtain the treated glass fiber cloth;

[0043] Step 2: 4 g of phenolic resin and 2.5 g of benzoxazine resin are added to a container, and then 0.5 g of 4-dodecylresorcin is added, and the mixture is stirred in an oil bath, and the mixture is kept at a constant temperature of 100 ° C for 3 h, and then the container is cooled to 55 ° C for 4 h. After the reaction is completed, a modified phenolic resin is obtained, and 575 g of the modified phenolic resin, 12 g of a composite curing agent and 7 g of a dispersant are mixed and stirred for 4 h to obtain a composite resin;

[0044] Step 3: Add the treated glass fiber cloth into the composite resin and soak it for 5 hours, take it out, put it in a mold, press it, and cure it to obtain a high-strength glass fiber board.

[0045] Example 2: This example discloses a method for preparing a composite flame retardant, comprising the following steps:

[0046] Q1: Under a nitrogen atmosphere, 22.62 g of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether was added to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heated in an oil bath at 45°C, and mechanically stirred at 280 rpm. Then, 2.12 g of phosphorus pentoxide was added within 25 min. After the addition was completed, the speed was reduced to 220 rpm, and the temperature was raised to 70°C for reaction for 20 min, and then the temperature was continued to be raised to 80°C for reaction for 4 h. Distilled water was added, the speed was increased to 240 rpm, and hydrolysis was carried out for 45 min to obtain a crude product.

[0047] Q2: Add 1.84 g of the crude product to 8 mL of anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt%, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt% to the supernatant, filter, wash, and dry at 90°C for 72 h to obtain a composite flame retardant.

[0048] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0049] S1: Add 250 mL of tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add 11 g of tetrafluorophthalic acid, 20 g of dicyclohexylcarbodiimide and 5 g of 2-dimethylaminopyridine in sequence under an ice-water bath, stir thoroughly for 4 h until completely dissolved, react for 2 h, and filter to obtain reactant 1;

[0050] S2: Add 23.5 g of hexamethylenediamine dissolved in 50 mL of tetrahydrofuran into the container, and slowly add 12.45 g of reactant 1 under ice bath conditions. After the addition is completed, react for 4 hours, then heat to 70°C and continue to react for 5 hours. After the reaction is completed, rotary evaporate, add dichloromethane to dissolve, filter, wash with deionized water to pH = 7, dry with anhydrous sodium sulfate, filter, and rotary evaporate to obtain a composite curing agent.

[0051] This embodiment discloses a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0052] Step 1: Add 4 g of the composite flame retardant to 10 mL of deionized water, disperse it by ultrasonic for 15 min, add glass fiber cloth, and dry it at 70 ° C for 10 h to obtain the treated glass fiber cloth;

[0053] Step 2: Add 3g of phenolic resin and 2g of benzoxazine resin to a container, then add 0.75g of 4-dodecylresorcinol, stir in an oil bath, keep constant temperature at 100°C for 3h, then cool the container to 55°C for 4h, after the reaction, obtain a modified phenolic resin, mix and stir 510g of the modified phenolic resin, 10g of the composite curing agent and 9g of the dispersant for 4h to obtain a composite resin;

[0054] Step 3: Add the treated glass fiber cloth into the composite resin and soak it for 5 hours, take it out, put it in a mold, press it, and cure it to obtain a high-strength glass fiber board.

[0055] Example 3: This example discloses a method for preparing a composite flame retardant, comprising the following steps:

[0056] Q1: Under a nitrogen atmosphere, 33.94 g of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether was added to a container equipped with a mechanical stirrer, a thermometer and a condensation reflux device, heated in an oil bath at 45°C, and mechanically stirred at 280 rpm. Then, 3.08 g of phosphorus pentoxide was added within 25 min. After the addition was completed, the speed was reduced to 220 rpm, and the temperature was raised to 70°C for reaction for 20 min, and then the temperature was continued to be raised to 80°C for reaction for 4 h. Distilled water was added, the speed was increased to 240 rpm, and hydrolysis was carried out for 45 min to obtain a crude product.

[0057] Q2: Add 2.32 g of the crude product to 10 mL of anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt%, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt% to the supernatant, filter, wash, and dry at 90°C for 72 h to obtain a composite flame retardant.

[0058] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0059] S1: Add 300 mL of tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add 12.2 g of tetrafluorophthalic acid, 22.84 g of dicyclohexylcarbodiimide and 6.16 g of 2-dimethylaminopyridine in an ice-water bath, stir well for 4 h until completely dissolved, react for 2 h, and filter to obtain reactant 1;

[0060] S2: Add 45g of hexamethylenediamine dissolved in 75mL of tetrahydrofuran into the container, and slowly add 15.68g of reactant 1 under ice bath conditions. After the addition is completed, react for 4h, then heat to 70°C and continue to react for 5h. After the reaction is completed, evaporate by rotary evaporation, add dichloromethane to dissolve, filter, wash with deionized water to pH=7, dry with anhydrous sodium sulfate, filter, and evaporate by rotary evaporation to obtain a composite curing agent.

[0061] This embodiment discloses a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0062] Step 1: Add 6 g of composite flame retardant to 13 mL of deionized water, disperse by ultrasonic for 15 min, add glass fiber cloth, and dry at 70 ° C for 10 h to obtain treated glass fiber cloth;

[0063] Step 2: Add 5g of phenolic resin and 3g of benzoxazine resin to a container, then add 0.25g of 4-dodecylresorcinol, stir in an oil bath, keep constant temperature at 100°C for 3h, then cool the container to 55°C for 4h, after the reaction, obtain a modified phenolic resin, mix and stir 625g of the modified phenolic resin, 14g of a composite curing agent and 5g of a dispersant for 4h to obtain a composite resin;

[0064] Step 3: Add the treated glass fiber cloth into the composite resin and soak it for 5 hours, take it out, put it in a mold, press it, and cure it to obtain a high-strength glass fiber board.

[0065] Embodiment 4: This embodiment discloses a method for preparing a composite flame retardant, comprising the following steps:

[0066] Q1: Under a nitrogen atmosphere, 25.45 g of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether was added to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heated in an oil bath at 45°C, and mechanically stirred at 280 rpm. Then, 2.36 g of phosphorus pentoxide was added within 25 min. After the addition was completed, the speed was reduced to 220 rpm, and the temperature was raised to 70°C for reaction for 20 min, and then the temperature was continued to be raised to 80°C for reaction for 4 h. Distilled water was added, the speed was increased to 240 rpm, and hydrolysis was carried out for 45 min to obtain a crude product.

[0067] Q2: Add 1.96 g of the crude product to 8.5 mL of anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt%, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt% to the supernatant, filter, wash, and dry at 90°C for 72 h to obtain a composite flame retardant.

[0068] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0069] S1: Add 260 mL of tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add 11.4 g of tetrafluorophthalic acid, 20.72 g of dicyclohexylcarbodiimide and 5.23 g of 2-dimethylaminopyridine in an ice-water bath, stir well for 4 h until completely dissolved, react for 2 h, and filter to obtain reactant 1;

[0070] S2: Add 28g of hexamethylenediamine dissolved in 60mL of tetrahydrofuran into the container, and slowly add 13.12g of reactant 1 under ice bath conditions. After the addition is completed, react for 4h, then heat to 70°C and continue to react for 5h. After the reaction is completed, rotary evaporate, add dichloromethane to dissolve, filter, wash with deionized water to pH=7, dry with anhydrous sodium sulfate, filter, and rotary evaporate to obtain a composite curing agent.

[0071] This embodiment discloses a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0072] Step 1: Add 4.5 g of the composite flame retardant to 11 mL of deionized water, disperse by ultrasonic for 15 min, add glass fiber cloth, and dry at 70 ° C for 10 h to obtain the treated glass fiber cloth;

[0073] Step 2: Add 3.5g of phenolic resin and 2.2g of benzoxazine resin into a container, then add 0.3g of 4-dodecylresorcinol, stir in an oil bath, keep constant temperature at 100°C for 3h, then cool the container to 55°C for 4h, after the reaction, obtain a modified phenolic resin, mix and stir 545g of the modified phenolic resin, 11g of a composite curing agent and 8g of a dispersant for 4h to obtain a composite resin;

[0074] Step 3: Add the treated glass fiber cloth into the composite resin and soak it for 5 hours, take it out, put it in a mold, press it, and cure it to obtain a high-strength glass fiber board.

[0075] Example 5: This example discloses a method for preparing a composite flame retardant, comprising the following steps:

[0076] Q1: Under a nitrogen atmosphere, 27.78 g of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether was added to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heated in an oil bath at 45°C, and mechanically stirred at 280 rpm. Then, 2.7 g of phosphorus pentoxide was added within 25 min. After the addition was completed, the speed was reduced to 220 rpm, and the temperature was raised to 70°C for reaction for 20 min, and then the temperature was continued to be raised to 80°C for reaction for 4 h. Distilled water was added, the speed was increased to 240 rpm, and hydrolysis was carried out for 45 min to obtain a crude product.

[0077] Q2: Add 2.2 g of the crude product to 9.5 mL of anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt%, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide at a mass fraction of 15 wt% to the supernatant, filter, wash, and dry at 90°C for 72 h to obtain a composite flame retardant.

[0078] This embodiment discloses a method for preparing a composite curing agent, comprising the following steps:

[0079] S1: Add 280 mL of tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add 12 g of tetrafluorophthalic acid, 21.93 g of dicyclohexylcarbodiimide and 6.07 g of 2-dimethylaminopyridine in an ice-water bath, stir well for 4 h until completely dissolved, react for 2 h, and filter to obtain reactant 1;

[0080] S2: Add 42.3 g of hexamethylenediamine dissolved in 55 mL of tetrahydrofuran into the container, and slowly add 14.93 g of reactant 1 under ice bath conditions. After the addition is completed, react for 4 hours, then heat to 70°C and continue to react for 5 hours. After the reaction is completed, rotary evaporate, add dichloromethane to dissolve, filter, wash with deionized water to pH = 7, dry with anhydrous sodium sulfate, filter, and rotary evaporate to obtain a composite curing agent.

[0081] This embodiment discloses a method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, comprising the following steps:

[0082] Step 1: Add 5.5 g of the composite flame retardant to 12 mL of deionized water, disperse it by ultrasonic for 15 min, add glass fiber cloth, and dry it at 70 ° C for 10 h to obtain the treated glass fiber cloth;

[0083] Step 2: Add 4.5g of phenolic resin and 2.7g of benzoxazine resin into a container, then add 0.6g of 4-dodecylresorcinol, stir in an oil bath, keep constant temperature at 100°C for 3h, then cool the container to 55°C for 4h, after the reaction, obtain a modified phenolic resin, mix and stir 600g of the modified phenolic resin, 13g of a composite curing agent and 6g of a dispersant for 4h to obtain a composite resin;

[0084] Step 3: Add the treated glass fiber cloth into the composite resin and soak it for 5 hours, take it out, put it in a mold, press it, and cure it to obtain a high-strength glass fiber board.

[0085] Comparative Example 1: Compared with Example 1, in the process of preparing the high-strength glass fiber board in Comparative Example 1, no composite flame retardant is added, and other conditions remain unchanged.

[0086] Comparative Example 2: Compared with Example 1, in the process of preparing the high-strength glass fiber board in Comparative Example 2, no composite curing agent is added, and other conditions remain unchanged.

[0087] Comparative Example 3: Compared with Example 1, in the process of preparing the high-strength glass fiber board, Comparative Example 3 uses phenolic resin instead of modified phenolic resin, and other conditions remain unchanged.

[0088] Experimental example: The combustion performance of the sample was tested according to GB 8624-2012, and the mechanical properties of the sample were tested according to HG / T3849-2008. The test results are shown in Table 1:

[0089] Table 1

[0090] project Combustion performance grade Tensile strength / MPa Example 1 A1 583.4 Example 2 A1 581.2 Example 3 A1 579.6 Example 4 A1 579.3 Example 5 A1 578.9 Comparative Example 1 A2 521.3 Comparative Example 2 A2 520.9 Comparative Example 3 A2 521.7

[0091] From the test results in Table 1, it can be seen that the glass fiber boards prepared in Examples 1-5 of the present invention have excellent mechanical properties and flame retardant properties. From the comparison between Comparative Example 1 and Examples 1-5, it can be seen that the addition of a composite flame retardant can effectively improve the mechanical properties and flame retardant properties of the glass fiber board; from the comparison between Comparative Example 2 and Examples 1-5, it can be seen that the addition of a composite curing agent can effectively improve the mechanical properties and flame retardant properties of the glass fiber board; from the comparison between Comparative Example 3 and Examples 1-5, it can be seen that the use of a modified phenolic resin can effectively improve the mechanical properties and flame retardant properties of the glass fiber board.

[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0093] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth, characterized in that: The following steps are involved: Step 1: adding the composite flame retardant to deionized water, and after ultrasonic dispersion, adding glass fiber cloth, and drying to obtain treated glass fiber cloth; Step 2: adding phenolic resin and benzoxazine resin into a container, then adding 4-dodecylresorcinol, stirring in an oil bath, reacting at a constant temperature, then cooling the container to react, after the reaction is completed, a modified phenolic resin is obtained, and the modified phenolic resin, a composite curing agent and a dispersant are mixed and stirred to obtain a composite resin; Step 3: adding the treated glass fiber cloth into the composite resin for impregnation, taking it out, placing it in a mold, pressing it, and curing it to obtain a high-strength glass fiber board; The preparation process of the composite flame retardant is as follows: using 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether as the main raw material and phosphorus pentoxide as the phosphorylation agent, forming a crude product containing a phosphate group through an esterification reaction; adding an alkalizing agent to the crude product, and the hydroxide ions of the alkalizing agent react with the hydrogen ions in the crude product to neutralize, thereby preparing the composite flame retardant; The preparation process of the composite curing agent is as follows: dicyclohexylcarbodiimide reacts with tetrafluorophthalic acid to obtain an intermediate, the intermediate reacts with 2-dimethylaminopyridine to obtain a reactant, and then the reactant reacts with hexamethylenediamine to obtain the composite curing agent.

2. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: Q1: Under a nitrogen atmosphere, add 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether to a container equipped with a mechanical stirrer, a thermometer and a condensing reflux device, heat in an oil bath, stir mechanically, and then add phosphorus pentoxide. After the addition is completed, reduce the speed, increase the temperature to react, then continue to increase the temperature to react, add distilled water, increase the speed, hydrolyze, and obtain a crude product; Q2: Add the crude product to anhydrous ethanol, add dropwise anhydrous ethanol solution containing potassium hydroxide, stir, centrifuge, continue to add dropwise anhydrous ethanol solution containing potassium hydroxide to the supernatant, filter, wash, and dry to obtain a composite flame retardant.

3. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 2, characterized in that: In the Q1, the mass ratio of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether and phosphorus pentoxide is (22.62-33.94):(2.12-3.08), the oil bath heating temperature is 40-50°C, the mechanical stirring speed is 250-280rpm, the time for adding phosphorus pentoxide is 20-25min, the speed is reduced to 200-220rpm, the temperature of the heating reaction is 68-70°C, the heating time is 15-20min, the heating reaction time is 3.5-4h, the temperature of the heating reaction is continued to be 75-80°C, the speed is increased to 230-240rpm, and the hydrolysis time is 30-60min.

4. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 2, characterized in that: In Q2, the usage ratio of the crude product and anhydrous ethanol is (1.84-2.32) g: (8-10) mL, the mass fraction of the anhydrous ethanol solution containing potassium hydroxide is 15 wt %, the drying temperature is 85-95° C., and the drying time is 48-72 h.

5. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 1, characterized in that: In the step 1, the dosage ratio of the composite flame retardant and deionized water is (4-6) g: (10-13) mL, the ultrasonic dispersion time is 10-15 min, the drying temperature is 50-70° C., and the drying time is 8-10 h.

6. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 1, characterized in that: In the step 2, the amount ratio of phenolic resin, benzoxazine resin and 4-dodecylresorcin is (3-5) g: (2-3) g: (0.25-0.75) g, the constant temperature insulation reaction temperature is 95-105° C., the reaction time is 2-3 h, the cooling reaction temperature is 50-55° C., the reaction time is 2-5 h, the amount ratio of modified phenolic resin, composite curing agent and dispersant is (510-625) g: (10-14) g: (5-9) g, and the mixing and stirring time is 2-4 h.

7. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 1, characterized in that: The preparation method of the composite curing agent comprises the following steps: S1: Add tetrahydrofuran to a container equipped with an electric stirrer, a dropping funnel and a spherical condenser, and then add tetrafluorophthalic acid, dicyclohexylcarbodiimide and 2-dimethylaminopyridine in sequence under an ice-water bath, stir until completely dissolved, react, and filter to obtain reactant 1; S2: Add hexamethylenediamine dissolved in tetrahydrofuran into a container, and slowly add reactant 1 under ice bath conditions. After the addition is completed, react, and then heat to continue the reaction. After the reaction is completed, rotary evaporate, dissolve, filter, wash, dry, filter, and rotary evaporate to obtain a composite curing agent.

8. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 7, characterized in that: In the S1, the dosage ratio of tetrahydrofuran, tetrafluorophthalic acid, dicyclohexylcarbodiimide and 2-dimethylaminopyridine is (250-300) mL: (11-12.2) g: (20-22.84) g: (5-6.16) g, the sufficient stirring time is 2-4 h, and the reaction time is 1-2 h.

9. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 7, characterized in that: In the S2, the dosage ratio of tetrahydrofuran, hexamethylenediamine and reactant 1 is (50-75) mL: (23.5-45) g: (12.45-15.68) g, the reaction time is 2-4 h, the heating reaction temperature is 60-80°C, the reaction time is 3-5 h, dichloromethane is added for dissolution, the mixture is washed with deionized water to pH = 7-8, and dried with anhydrous sodium sulfate.

10. The method for preparing a high-strength glass fiber board using flame-retardant fast-curing glass fiber cloth according to claim 1, characterized in that: In the step 3, the infiltration time is 3-5 hours.

Citation Information

Patent Citations

  • Novel high-efficiency heat dissipation single-sided pcb glass fiber board

    CN209944267U